Generation of low-energy neutrons cross-sections for the Monte Carlo code FLUKA and the deterministic code ActiWiz. (December 2020) - Frosio, Thomas; Magistris, Matteo; Theis, Chris; Vincke, Helmut
Abstract: Activation of material is of interest for waste treatment and hazard assessment. In particular, activation of printed circuit can lead to the production of radionuclides at an isomeric state, for example, coming from silver. In particle accelerators, the production of silver isomeric states mainly come from low energy neutrons, below 20 MeV. The quantification of activation and associated doses at CERN is based on the FLUKA and ActiWiz codes. In the FLUKA release 2011.2c, all branching ratios for isomer production were set at 50% by default. The present work provides a set of nuclide- and energy-dependent branching ratios, extracted from the library EAF-2010. In the ActiWiz release 3.3, the library JEFF3.1.1 was used for low energy neutron cross-sections. This study provides a new set of neutron cross-sections extracted from JEFF3.3, ENDFB/VIII.0 and EAF-2010 for future update of ActiWiz. Highlights: Computation of new production cross-sections for FLUKA and ActiWiz. Improvement of FLUKA isomer production branching ratios.